2020
DOI: 10.1108/ijse-04-2020-0238
|View full text |Cite
|
Sign up to set email alerts
|

Does credit boost agricultural performance? Evidence from Vietnam

Abstract: PurposeThis study investigates the short-run and long-run impacts of agricultural credit on Vietnam's agricultural GDP over the period 2004:Q4–2016:Q4, with the incorporation of agricultural labor, public investment and rainfall as important determinants of agricultural GDP.Design/methodology/approachThis study applies the indicator saturation (IS) break tests and the autoregressive distributed lag (ARDL) bounds test with structural breaks to examine the credit–agricultural performance nexus. The causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
(59 reference statements)
1
14
0
1
Order By: Relevance
“…The agricultural sector easily passes in most literature as the mainstay of the economy for many developing countries (Adekunle and Ndukwe, 2018). The agricultural sector in these economies is the most crucial sector and perhaps indispensable in generating output and employment (Anh et al, 2020). Apart from impacting directly on economic growth, Ndor et al (2020) asserted that agriculture sustains economic development in all ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…The agricultural sector easily passes in most literature as the mainstay of the economy for many developing countries (Adekunle and Ndukwe, 2018). The agricultural sector in these economies is the most crucial sector and perhaps indispensable in generating output and employment (Anh et al, 2020). Apart from impacting directly on economic growth, Ndor et al (2020) asserted that agriculture sustains economic development in all ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…Osabohien et alii (2020) ont confirmé que le développement financier a un impact positif significatif sur les performances agricoles à long et à court terme. Des études ont affirmé que les crédits agricoles impactent positivement sur la productivité agricole (Anh et al, 2020 ;Seven & Tumen, 2020). Au Vietnam, Anh et alii (2020) ont établi un impact positif à court et à long terme du crédit agricole sur la production agricole.…”
Section: La Théorie Empiriqueunclassified
“…A substantial number of recent studies were devoted to investigating the effects of agricultural credits on agricultural productivity. As regards agricultural productivity, a great deal of research (Siriram, 2007;Das et al, 2009;Ali et al, 2014;Misra et al, 2016;Rehman et al, 2017;Seven &Tumen, 2020;Tuan Anh et al, 2020;Chandio et al, 2021, Manoharan & Varkey, 2021 identified the role of credits on agricultural productivity. While some of these studies used farm-level data, some of them has identified and addressed linkages focusing specifically on country-level data.…”
Section: Introductionmentioning
confidence: 99%